"Nobody's Ever Told Me That:" Women's Experiences with Shared Decision-making when Accessing Contraception. Issue 2 (28th January 2021) - Meier, Stephanie; Sundstrom, Beth; Delay, Cara; DeMaria, Andrea L.
ABSTRACT: Half of all pregnancies in the United States are unintended. Contraceptive methods are effective in reducing unintended pregnancy burden. The shared decision-making model serves as best practice when choosing among healthcare options, and may be appropriate when considering contraceptive options. This study examined women's experiences with shared decision-making in contraceptive use dynamics. Researchers analyzed 38 interviews with women of reproductive age (range: 19–50 years) living in South Carolina (May-November 2016). Researchers completed a constant comparative method of data analysis using HyperRESEARCH 3.7.3 to explore reproductive-aged women's contraceptive decision-making. Shared decision-making provided a conceptual framework for analysis. Gaps in contraceptive knowledge, especially method effectiveness, impacted participants' experiences with contraception. Although participants believed they had adequate information, findings suggest they may not be fully informed about existing contraceptive options. Participants wanted options; however, results indicated women may not be actively involved in choosing contraception. Nuanced beliefs about contraception demonstrated preferences for patient-provider communication within the broader context of reproductive health and individual lifestyle needs. Findings from this study offer theoretical and practical recommendations to guide shared decision-making during contraceptive consultations to empower women in making informed and lifestyle-appropriate contraceptive choices.